Towards Life Cycle Sustainability Management 2011
DOI: 10.1007/978-94-007-1899-9_8
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of an Actor’s Perspective in LCA

Abstract: This paper is an argumentation for adding an actor's perspective to lifecycle assessment (LCA). The need for this perspective stem from a criticism about the usefulness of LCA interpretation methods comparing the relative contribution of life-cycle phases of a product. Our argumentation is based on four previously published studies providing practical examples of how value chain actors' influence may be considered in an LCA and the benefit of doing so. Manufacturing sector examples show how one company's influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…More information on the LCA methodology can be found in Heijungs et al (1992a, b), Consoli et al (1993), Lindfors et al (1995), van den Berg et al (1995), Guinée et al (2001), Baumann and Tillman (2002) and Rebitzer et al (2004).…”
Section: Methodsmentioning
confidence: 99%
“…More information on the LCA methodology can be found in Heijungs et al (1992a, b), Consoli et al (1993), Lindfors et al (1995), van den Berg et al (1995), Guinée et al (2001), Baumann and Tillman (2002) and Rebitzer et al (2004).…”
Section: Methodsmentioning
confidence: 99%
“…Our approach is designed both for documenting implicit actors in flow models, and for revealing nonintuitive connections. The approach is based on the presented extended terminology for flows and humans, on the presented constructivist sociomaterialism, and on explorative case studies (cf., Baumann et al., 2015). From the case studies, we found it useful to outline concepts (Sections 5.1 and 5.2) and a procedure (Section 5.3).…”
Section: A Sociomaterials Approach For Identifying Relations Between ...mentioning
confidence: 99%
“…To help address the many challenges that arise during product development, many designers use guidelines, checklists and analytical tools. However, the use and application of eco-design tools, methods and techniques by small sized firms is limited (Baumann et al, 2011;Knight & Jenkins, 2009). Almost none of the interviewed design entrepreneurs used tools, such as Ted's Ten (Textile Environment Design, 2006), the Nike Maker App (Centre for Sustainable Fashion, 2013), or the Sustainable Apparel Coalition's Higg Index (Sustainable Apparel Coalition, 2017), and the majority were not aware of these tools.…”
Section: Prototypes and Product Developmentmentioning
confidence: 99%